Analisis Studi Pada Kemandirian Belajar Siswa - Ilham Muhammad; Fadli Agus Triansyah (Pusat Riset dan Inovasi Nasional, 2023)
Student learning independence plays a very important role in modern education. This triggers a lot of research related to learning independence. The aim of this research is to capture the research landscape related to learning independence. The method used is bibliometric analysis. The data is obtained from the enhanced Scopus database. The results showed that the number of publications related to learning independence increased every year from 2018 to 2020. The highest number of documents was in the Indonesian state, the highest number of documents were in the institution or university